Salmonella infection in clinically healthy dogs in Makurdi, Benue State, North-central Nigeria: A potential source of infection to humans - Akwuobu, Chinedu Adive; Agbo, Joseph Odeh; Ofukwu, Raphael Agbo-Peters (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The present study was initiated to ascertain the level of shedding of salmonellae by dogs in Makurdi area and to highlight the risk of infection for dog-owners. Materials and Methods: Rectal swabs from 200 dogs from different locations in the study area were examined in the study. The samples were cultured for salmonellae using RappaportVassiliadis enrichment broth (Oxoid) and brilliant green agar (Oxoid). Suspected Salmonella isolates were serologically identified. Results: Overall, Salmonellae organisms were isolated from 11 (5.5%) of the 200 dogs sampled. Prevalence rates of 5.6% and 4.5% were recorded for apparently healthy and clinically sick dogs, respectively. Salmonella was respectively isolated from 4.1% to 9.1% of male and female dogs. Dogs aged 4 years and above recorded the highest prevalence rate. The study revealed a low prevalence rate in Nigerian local breed (mongrels) and high prevalence rates in exotic breeds of dogs. Conclusion: The isolation of salmonellae in apparently healthy and clinically sick dogs in this study indicates a carrier status which may constitute a serious problem in disease control in the study area. The lower prevalence rate of Salmonella infection in mongrels could be an indication of resistance to Salmonella in local breeds of dogs and should generate interest in research in the pathogenicity and pathogenesis of salmonellae in mongrels. http://doi.org/10.5455/javar.2018.e291